103k views
2 votes
Represent the arithmetic series using the recursive formula. 94, 81, 68, 55, …

f(n) = f(n − 1) + (13)
f(n) = f(n − 1) + (−13)
f(n) = f(1) + (13)
f(n) = f(1) + (−13)

2 Answers

2 votes

Answer:

f(n)=f(n-1)=(-13)

Explanation:

got it right on flvs

User PsychOle
by
5.8k points
4 votes

Answer:


f(n) = f(n - 1) - 13

Explanation:

The given sequence is 94, 81, 68, 55, …

We can observe that, there is a constant difference among the subsequent terms:


d = 81 - 94 = - 13

The sequence is therefore an arithmetic sequence with first term:


f(1) = 94

The recursive formula is given by;


f(n) = f(n - 1) + d

We just have to plug in d=-13 to get:


f(n) = f(n - 1) - 13

User Omri Bernstein
by
6.4k points